Hindu Jurisprudence as The Basis and Source of Nepalese Family Laws: An Investigation - Rajeev Kumar Singh; Jivesh Jha (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
Hindu jurisprudence has played an important role in the formation of the basis and source of family law in Nepal. This article conducts an in-depth investigation of how Hindu legal principles have influenced the regulation of family law in Nepal. Through careful analysis, it outlines the historical development of Hindu jurisprudence and the way its influence manifests in Nepal's family law provisions, particularly under the National Civil Code 2017. It explores the historical foundations of Hindu law and identifies its practical consequences in the Nepalese context, including possible incongruities between Hindu law and its regulations. In doing so, it provides a deep insight into the complexity of the interaction between Hindu legal traditions and the structure of family law in Nepal. This article discusses in detail the historical development of the recognition of Hindu jurisprudence under Nepal's family law. It illustrates how key laws, such as legal arrangements for marriage, adoption, maintenance, or division, are influenced by Hindu scriptures. The article explains the provisions of the family law (enacted under the National Civil Code, 2017) in light of Hindu laws and practices prevalent in India. It also presents inconsistencies between Hindu laws and embedded regulations. This research approach integrates as legal research with a socio-legal approach, and a thorough literature review to uncover the impact of Hindu jurisprudence on Nepali family law, particularly under the National Civil Code 2017. Through these methods, this article strengthens the understanding of the complex relationship between Hindu legal tradition and family law regulation in Nepal. The conclusion of this study highlights the importance of understanding the practical implications of the application of Hindu law in the context of Nepalese family law, as well as emphasizing the need for consistency and harmonization between Hindu law and applicable regulations to achieve justice in Nepal's evolving family law system.